Functional Urban Areas as the Focus of Development Policy in Poland - Kaczmarek, Tomasz (Rozwój Regionalny i Polityka Regionalna, 2015)
This article presents the premises, current status and the prospects of using functional urban areas as the focus of Poland's development policy. For the past 10 years, cities, especially large ones, have been increasingly impacting on their surrounding areas defined as functional urban areas. The size of those areas is determined by the process of suburbanisation. The article emphasises the issue of uncoordinated development of functional urban areas surrounding core cities and on grassroot and top-down attempts to integrate their development.